Antioxidase-mimetic artificial biotubes for anti-inflammatory healing and regeneration of vascular injury; Biomaterials; Vol. 327 - Guliyaer Aini; Jianmei Ren; Haojie Xu; Yang Gao; Tiantian Li; Lang Ma; Li Qiu; Sheremet E. S. Evgeniya Sergeevna; Shuang Li; Cheng Chong; Ma Tian; Zhao Changsheng (2026, 2026)
Title screen